Characterizing seawater oxygen isotopic variability in a regional ocean modeling framework: Implications for coral proxy records. (30th November 2015) - Stevenson, S.; Powell, B. S.; Merrifield, M. A.; Cobb, K. M.; Nusbaumer, J.; Noone, D.
Abstract: Reconstructions of the El Niño–Southern Oscillation (ENSO) are often created using the oxygen isotopic ratio in tropical coral skeletons ( δ 18 O). However, coral δ 18 O can be difficult to interpret quantitatively, as it reflects changes in both temperature and the δ 18 O value of seawater. Small‐scale (10–100 km) processes affecting local temperature and seawater δ 18 O are also poorly quantified and contribute an unknown amount to intercoral δ 18 O offsets. A new version of the Regional Ocean Modeling System capable of directly simulating seawater δ 18 O (isoROMS) is therefore presented to address these issues. The model is used to simulate δ 18 O variations over the 1979–2009 period throughout the Pacific at coarse ( O (50 km)) resolution, in addition to 10 km downscaling experiments covering the central equatorial Pacific Line Islands, a preferred site for paleo‐ENSO reconstruction from corals. A major impact of downscaling at the Line Islands is the ability to resolve fronts associated with tropical instability waves (TIWs), which generate large excursions in both temperature and seawater δ 18 O at Palmyra Atoll (5.9°N, 162.1°W). TIW‐related sea surface temperature gradients are smaller at neighboring Christmas Island (1.9°N, 157.5°W), but the interaction of mesoscale features with the steep island topography nonetheless generates cross‐island temperature differences of up to 1°C. These nonlinear processes alter the slope of the salinity:seawater δ 18 O relationship at Palmyra and Christmas, as well as affect the relation between coral δ 18 O and indices of ENSO variability. Consideration of the full physical oceanographic context of reef environments is therefore crucial for improving δ 18 O‐based ENSO reconstructions. Key Points: A new, isotope‐enabled version of ROMS is presented Mesoscale processes significantly impact coral proxy sites Downscaling changes the ENSO‐ δ 18 O relation in the central tropical Pacific